A Comprehensive Study of Clinical, Biochemical, Radiological, Vascular, Cardiac, and Sleep Parameters in an Unselected Cohort of Patients With Acromegaly Undergoing Presurgical Somatostatin Receptor Ligand Therapy - Anand K. Annamalai; Alison Webb; Narayanan Kandasamy; Maysoon Elkhawad; Samantha Moir; Fakhar Z. Khan; Kaisa Mäki-Petäjä; Emma L. Gayton; Christopher Strey; Samuel O’Toole; Shaumya Ariyaratnam; David Halsall; et al. (2013)
Attainment of safe GH and IGF-1 levels is a central goal of acromegaly management.